Hubungan Penggunaan Media Audio-Visual dengan Minat Belajar Siswa Pendidikan Agama Buddha di SMA Negeri 1 Donorojo - Mayadi Mayadi; Kabri Kabri; Budiyanto Budiyanto (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Learning interest is an important psychological factor that determines the success of learning, including in Buddhist Religious Education, which contains many abstract and philosophical concepts such as the Four Noble Truths, the Noble Eightfold Path, and the Law of Kamma. Preliminary observation at SMA Negeri 1 Donorojo showed that learning was still dominated by the lecture method, while the use of audio-visual media had not been carried out optimally and consistently, raising questions about its relationship with students' learning interest. This study aims to describe the level of audio-visual media use, describe students' learning interest, and analyze the relationship between the two in Buddhist Religious Education learning at SMA Negeri 1 Donorojo. This study used a quantitative correlational approach with a saturated sampling technique involving 39 Buddhist students as both the population and the sample. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, then analyzed using normality tests, linearity tests, and Pearson Product Moment correlation with the help of SPSS. The results showed that the use of audio-visual media was in the high category (mean = 101.25) and students' learning interest was also in the high category (mean = 99.15). The correlation test obtained a coefficient of r = 0.933 with a significance of < 0.001, indicating a very strong positive relationship between the two variables, with a coefficient of determination of 87.0%. These findings reinforce Mayer's Cognitive Theory of Multimedia Learning and provide practical implications for teachers to utilize audio-visual media in a planned manner in Buddhist Religious Education.